PERBANDINGAN PERFORMA DUA STRAIN AYAM JANTAN TIPE MEDIUM YANG DIBERI RANSUM KOMERSIAL BROILER - Fazar Ardiansyah; Syahrio Tantalo; Khaira Nova (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2013)
This study aims to determine the best strain of the performance of medium type roosters fed commercial broiler rations. This study conducted for 7 weeks from 19 may to 06 july 2012, in the chicken coop department of animal husbandry, faculty of agriculture, University of Lampung. The chicken is a rooster who used medium type strain Isa Brown and Lohman each as much as 100 individuals. This study compared two treatments are different strains rooster medium type Isa Brown rooster and Lohman medium type srtain. Data obtained from the study were analyzed using student t-test on the real level of 5%. The variables measured were ration consumpion, body weight gain, conversion ratio, and income over feed cost (IOFC). The results showed that the strain Isa Brown had ration consumption and body weight were significantly (P<0.05) higher than Lohman strain, but the conversion ratio and the type of medium IOFC cock both strains were not significantly (P>0.05) . Keyword: Performance, strain, roosters medium type, and commercial broiler ration.